Daemonorops draco Blume Induces Apoptosis Against Acute Myeloid Leukemia Cells via Regulation of the miR-216b/c-Jun - Park, Moon Nyeo; Jeon, Hee Won; Rahman, Md. Ataur; Park, Se Sun; Jeong, Se Yun; Kim, Ki Hyun; Kim, Sung-Hoon; Kim, Woojin; Kim, Bonglee (Frontiers in Oncology, 2022)
Daemonorops draco Blume (DD), also called dragon’s blood, has been used as a traditional Korean medicine, especially for relieving pain caused by wound infection. Recently, it has been described that DD has antibacterial and analgesic effects. In this study, the underlying anticancer effect of DD associated with apoptosis was investigated in acute myeloid leukemia cell lines U937 and THP-1. DD exhibited cytotoxic effects and induced apoptosis in U937 and THP-1 cells. Moreover, DD treatment significantly reduced mitochondrial membrane potential (ΔΨ). The protein expression of cleaved poly(ADP-ribose) polymerase, cleaved caspase-3, p-H2A.X, CCAAT/enhancer-binding protein (CHOP), and activating transcription factor 4 was upregulated by DD treatment. Consistently, DD-treated cells had increased reactive oxygen species (ROS) level in a concentration-dependent manner via miR-216b activation in association with c-Jun inhibition. N-acetyl-L-cysteine pretreatment reversed the cytotoxic effect of DD treatment as well as prevented ROS accumulation. Collectively, the results of this study suggest that the anticancer effect of DD in AML was mediated by CHOP-dependent apoptosis along with ROS accumulation and included upregulation of miR-216b followed by a decrease in c-Jun.